Efektivitas Media Pembelajaran Interaktif Articulate Storyline dengan Media Powerpoint Terhadap Hasil Belajar Materi Substansi Genetika Siswa Kelas XII - Chatarina Eka Berliyanti Putri; Sunaryo; Sonny Kristianto (Journal of Natural Sciences and Learning, 2022)
The study aims to find a comparison of the effectiveness of interactive learning media with powerpoint media on the results of studying the genetic substance of class XII students at Hang Tuah 4 Surabaya high school. The method used in this study is an experiment with research design is a nonfunctional control design group. The population in this study is 33 XII High School Science students Hang Tuah 4 Surabaya. The sample used in the study is to group into two large groups by odd absenbs and even Numbers.Research obtained from: (1) the average student study results from both groups, experiment groups 1 and experiment groups 2, were obtained that the average for experiment groups 1 of 80,63, for experiment groups 2 of 65.88. (2) based on the t test results on both groups, the result of thitung gained by 0.017, in which case it is stated that thitung is smaller than the ttabel 0.05. Based on the average results of student study and hypothetical tests made by researchers it results that the use of interactive learning medium suggests a postif and is more effective in the increased study of students the genetic substance of a class XII Science 2 High School Hang Tuah 4 Surabaya